2022
DOI: 10.3390/coatings12030366
|View full text |Cite
|
Sign up to set email alerts
|

Ti/SnO2-Sb2Ox-TiO2 Electrodeposited from Methanesulfonate Electrolytes: Preparation, Properties, and Performance

Abstract: In this study, Ti/SnO2-Sb2Ox-TiO2 electrodes were produced using a sol-enhanced electrodeposition technique from methanesulfonate electrolytes. The surface microstructures of Ti/SnO2-Sb2Ox-TiO2 were observed, and their phase constituents were determined. The surface features were analyzed by X-ray photoelectron spectroscopy. Linear sweep voltammetry and degradation tests were also conducted to determine the degradation performance. The results show that the addition of TiO2 sol affects the microstructures of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Figure 4b-d revealed that Sb 3+ and Sb 5+ were present in the SnO 2 -Sb coatings, corresponding to the two oxidation states for Sb that existed in the SnO 2 lattice. Moreover, O lat (i.e., lattice oxygen species) and O ads (hydroxyl oxygen species) are the two oxygen species that were identified, consistent with previous research [31].…”
Section: Effects Of Current Densitysupporting
confidence: 91%
“…Figure 4b-d revealed that Sb 3+ and Sb 5+ were present in the SnO 2 -Sb coatings, corresponding to the two oxidation states for Sb that existed in the SnO 2 lattice. Moreover, O lat (i.e., lattice oxygen species) and O ads (hydroxyl oxygen species) are the two oxygen species that were identified, consistent with previous research [31].…”
Section: Effects Of Current Densitysupporting
confidence: 91%
“…The removal rate of adsorbable organic iodide reached 80% in the case of Ti/SnO 2 –SbBi, but increased to 82% in the case of Ti/TiO 2 –NT/SnO 2 –SbBi. Zhang et al [ 160 ] also demonstrated that the addition of TiO 2 sol caused the deep oxidation of Sb and produced more adsorbed oxygen on the electrode surface. The good surface characteristics and well‐dispersed TiO 2 in the TiO 2 ‐modified Ti/SnO 2 –Sb 2 O x –TiO 2 electrode coating make it have the best electrocatalytic performance, and its uniform coating surface extends the life of the electrode.…”
Section: Ti/sno2 Electrodementioning
confidence: 99%
“…The global cost of corrosion is estimated to be 3%-5% of the global gross domestic product (GDP), not including individual safety or environmental consequences. To reduce the corrosion cost and to avoid catastrophic corrosion consequences, abundant corrosion studies have been performed and effective corrosion control practices [18][19][20][21][22] have been used to understand the corrosion fundamentals, to inspect the corrosion performance of structural components or materials, to evaluate the safety issues, to analyze and report the corrosion failure, and to develop advanced corrosion control techniques. This benefits the selection and design of the corrosion-resistant materials used in modern society, and their safety assessment.…”
mentioning
confidence: 99%
“…With the great efforts of the Guest Editor team, the enthusiastic support of the Editorial Board and the valuable contribution of the participates, this Special Issue has reached a milestone, successfully publishing 31 peer-reviewed papers. It covers a series of research areas ranging from the microstructure characterization of the studied materials which has a great impact on their corrosion performance [11,12], the corrosion behaviors and mechanisms of the structural or novel-designed materials in potential service environments [13][14][15][16][17], the development of new coatings acting as corrosion barriers to protect the materials [18][19][20][21][22], the corrosion model built to predict the corrosion progress of the material investigated [23], and other related areas [24][25][26][27].…”
mentioning
confidence: 99%